Latent free equivalent mDAGs - Evans, R (Mathematical Sciences Publishers, 2023)
We show that the marginal model for a discrete directed acyclic graph (DAG) with hidden variables is distributionally equivalent to another fully observable DAG model if and only if it does not induce any nontrivial inequality constraints.